2004
DOI: 10.1164/rccm.200306-789oc
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber and Reduced Cough with Phlegm

Abstract: Smoking is the major risk factor for chronic respiratory symptoms, but dietary factors may also play a role. Most studies of diet and lung disease have been cross-sectional and conducted in populations with a Western-style diet. We analyzed the relation between dietary intake at baseline and new onset of cough with phlegm in a population-based cohort of 63,257 middle-aged Chinese men and women initiated in Singapore between 1993 and 1998. Beginning in 1999, we ascertained respiratory symptoms by telephone inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 68 publications
4
84
1
1
Order By: Relevance
“…As noted by the authors, relatively little attention has been paid to soy intake in relation to respiratory or allergic diseases. [8][9][10][11] In a cross-sectional study of young adults in Australia, the consumption of soy beverage was associated with an increased prevalence of current asthma, doctor-diagnosed asthma and bronchial hyperresponsiveness. 8 In another cross-sectional study among Japanese pregnant women, dietary intakes of total soy product, soy protein, daidzein, and genistein in the fourth quartile (as compared to the first quartile), were independently associated with a reduced prevalence of allergic rhinitis, although no significant dose-response relations were observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by the authors, relatively little attention has been paid to soy intake in relation to respiratory or allergic diseases. [8][9][10][11] In a cross-sectional study of young adults in Australia, the consumption of soy beverage was associated with an increased prevalence of current asthma, doctor-diagnosed asthma and bronchial hyperresponsiveness. 8 In another cross-sectional study among Japanese pregnant women, dietary intakes of total soy product, soy protein, daidzein, and genistein in the fourth quartile (as compared to the first quartile), were independently associated with a reduced prevalence of allergic rhinitis, although no significant dose-response relations were observed.…”
mentioning
confidence: 99%
“…9 In a longitudinal study among middle-aged Chinese men and women, total soyfood and soy isoflavone (daidzein, genistein, and glycitein) intakes had modest inverse associations with incident cough plus phlegm. 10 Among asthmatic adults enrolled in a vaccination trial, the authors noted a cross-sectional association between high consumption of genistein and better lung function. 11 Overall, three studies out of four were cross-sectional, and the only longitudinal study was on cough plus phlegm (not asthma).…”
mentioning
confidence: 99%
“…Although previous epidemiological studies have implicated the antioxidant effects of flavonoids (especially from apples, tea and pears) in reducing lung function decline [62,63], increased dietary fibre has been linked to reduced respiratory symptoms [64], better lung function [59,60] and reduced respiratory mortality [65,66]. Surprisingly, in the study on mortality [65], the protective effect conferred by a high fibre diet was greater for respiratory deaths than for cardiovascular disease and cancer, further implicating an anti-inflammatory mechanism [66].…”
Section: The Hispanic Paradoxmentioning
confidence: 86%
“…Here we present data to suggest that the increased consumption of high-fibre foods such as legumes, primarily in the form of beans, may provide an alternate explanation for the Hispanic paradox [43,48,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Data on bean consumption shows that Hispanic subjects, who represent 11% of the USA population, are the largest consumers of beans (accounting for 33% of all consumption) [52].…”
Section: The Hispanic Paradoxmentioning
confidence: 99%
“…There is no consensus of prophylaxis for progression of COPD except for cigarette smoke cessation (Scanlon et al, 2000). Recently, some epidemiological studies demonstrated that dietary fiber mitigated cough and sputum in smokers and second hand smokers (Butler et al, 2004;David et al, 2005;Butler et al, 2006). Moreover, it has been demonstrated that intake of dietary fiber was associated with a better lung function and reduced prevalence of COPD (Kan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%